Sosialisasi UKM Kopma PB (Padang Bulan) sebagai media komunikasi terhadap minat calon anggota baru pada mahasiswa UIN Malang - Kurniawati, Lina (Maliki Interdisciplinary Journal, 2023)
In everyday life, we will never escape the term communication. Communication is a process of exchanging messages or information between two or more people to form a goal and purpose for their respective needs. In an organization, communication is very important in order to achieve the desired goals in an organization. Including a person's interest in an organization, there is a need for communication as a medium to channel a need or intention in that interest. One example of this is providing a public service in the form of socialization. This research aims to socialize the Kopma Padang Bulan student activity unit as a communication medium for the interest of prospective new members among Uin Malang students. This research was conducted using a direct data collection method where the author made direct observations on the subjects that the author had researched. By using this system, the author can more easily make these observations because the subjects studied by the researcher are easy to find. The results of this research observation show that communication has a very important role in organizations or student activity unit. In the socialization of UKM, communication becomes a medium for student interests, where one type of communication used is interpersonal communication. Communication as a medium for socializing student activity unit, namely Kopma Padang Bulan, towards the interests and interests of Uin Malang students to become new members of Kopma. This observation was carried out by maintaining the UKM Kopma stand with the aim of being an intermediary for convenience and providing direction and assistance to students who were interested in UKM Kopma.